Enhancing Human Rights Protections in Ukrainian Law Enforcement: National Compliance with EU Standards - Blahuta , Roman I.; Barabash, Olha O.; Zakharov , Vasyl P.; Kovalska, Mariia Yu.; Dobkina , Kateryna R. (Universitas Airlangga, 2024)
Ensuring human rights and freedoms is the primary task of national development in Ukraine and the main social values and freedoms that determine the need to ensure the transparent, efficient, and population-oriented functioning of all state institutions that ensure the protection of people's and citizens' rights. The purpose of this research is to identify the state of human rights protection and enforcement in law enforcement activities in EU countries and Ukraine and to outline trends for further improvement in human rights law enforcement activities. The methodological basis of the investigation is the dialectics of worldview and general and specific scientific methods for understanding national phenomena and legal realities. The research finds the promotion and protection of human rights and freedoms are foundational to effective law enforcement activities, requiring alignment with constitutional, legal, and international standards. The modernization of policing principles involves expanding the role of national institutions, fostering accountability, diversity and partnerships, while humanizing police activities to establish trust-based relations with citizens. The research further emphasizes the critical role of implementing these insights into the actual activities of Ukrainian law enforcement agencies for a more meaningful and impactful transformation in ensuring human rights and freedoms. The study is of great scientific and theoretical importance, since scientific achievements in this field define the general direction of its understanding of the state, making it possible to understand and identify new trends in the development of ensuring compliance with human rights and freedoms in the world.